Effects of Different Re-referencing Methods on Spontaneously Generated Ear-EEG - Choi, Soo-In; Hwang, Han-Jeong (Frontiers in Neuroscience, 2019)
In recent years, electroencephalography (EEG) measured around the ears, called ear-EEG, has been introduced to develop unobtrusive and ambulatory EEG-based applications. When measuring ear-EEGs, the availability of a reference site is restricted due to the miniaturized device structure, and therefore a reference electrode is generally placed near the recording electrodes. As the electrical brain activity recorded at a reference electrode closely placed to recording electrodes may significantly cancel or influence the brain activity recorded by the recording electrodes, an appropriate re-referencing method is often required to mitigate the impact of the reference brain activity. In this study, therefore, we systematically investigated the impact of different re-referencing methods on ear-EEGs spontaneously generated from endogenous paradigms. To this end, we used two ear-EEG datasets recorded behind both ears while subjects performed an alpha modulation task (eyes-closed and eyes-open) and two mental tasks (mental arithmetic and mental singing). The measured ear-EEGs were independently re-referenced using five different methods: i) all-mean, ii) contralateral-mean, iii) ipsilateral-mean, iv) contralateral-bipolar, and v) ipsilateral-bipolar. We investigated the changes in alpha power during eyes-open and eyes-closed tasks, as well as event-related (de)synchronization (ERD/ERS) during mental arithmetic and mental singing. To evaluate the effects of re-referencing methods on ear-EEGs, we also estimated the signal-to-noise ratios (SNRs) of the two ear-EEG datasets, as well as assessed the classification performance of the two mental tasks (mental arithmetic vs. mental singing). Overall patterns of changes in alpha power and ERD/ERS were similar among the five re-referencing methods, but the contralateral-mean method showed statistically higher SNRs than did the other methods for both ear-EEG datasets, except in the contralateral-bipolar method for the two mental tasks. In concordance with the SNR results, classification performance was also statistically higher for the contralateral-mean method than it was for the other re-referencing methods. The results suggest that employing contralateral mean information can be an efficient way to re-reference spontaneously generated ear-EEGs, thereby maximizing the reliability of ear-EEG-based applications in endogenous paradigms.